Tratamiento de residuos orgánicos generados en los laboratorios de química de la Universidad del Quindío (2002)
Within the Organic Chemistry Laboratory practices many residues are produces the majority are contaminants potencially hazard or dangerous. After the residue is caracterized, that is possible within practice realization of low scale, you can obtain the principal characteristics of that residue and it finishes with its treatment that depends on functional characterization and conduction of the residue. Next to that operation you should store the product in laber collector. The last operation is for toxic products for the environment.